Block rotations within the northern Peruvian Altiplano - Roperch, Pierrick (2008)
Counterclockwise tectonic rotations in the northern central Andes and clockwise rotations in the southern Central Andes have been systematically reported (see Roperch et al. 2006 and Arriagada et al., 2006 for a recent summary) and interpreted to be mostly driven by oroclinal bending associated with shortening in the Eastern Cordillera and in the subandean belt. Large counterclockwise rotations have been found in the Eastern Cordillera of Southern Peru (Gilder et al. 2003). While these rotations were initially attributed to a Cretaceous event of deformation, Gilder et al. (2003) interpreted these rotations to be coeval with the rotations found along the forearc (Roperch et al., 2006). Rotations along the forearc from Arequipa to Caravelli are larger than 40° and occurred mainly during the late Eocene - Oligocene. However, the lack of data within the Peruvian Altiplano precludes a good description of the spatial and temporal evolution as well as a clear understanding of the different tectonic processes leading to rotations. Here we report results from a paleomagnetic study from Nazca to Cusco (Figure 1). This transect corresponds to the location of the northern end of the Altiplano and a transition with the central Peruvian Andes. Near Cusco, the Eastern Cordillera is also strongly deflected toward the east with a complex deformation as shown by the curved fold and thrust system associated with the Manu Indenter.